Studi Komposisi Kimia Produk Pirolisis Kilat Off-grade Rubber dengan Katalis Ni/Ga-SBA-15 - Three Uli Sevilla Sitohang; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo (Chemistry Department, 2025)
This study investigated the chemical composition of flash pyrolysis products from off-grade rubber, a low-quality byproduct of natural rubber processing, with and without Ni/Ga-SBA-15 catalyst. The flash pyrolysis was conducted under helium using pyrolysis–Gas Chromatography/Mass Spectrometry (Py-GC/MS) at 200 °C and 300 °C. The off-grade rubber contained 23.62 ± 2.26 wt. % moisture and 11.24 ± 1.09 wt. % ash. FTIR analysis revealed the functional groups in the rubber sample, including =C–H, -CH₂, C=O, C=C, -CH₃, C–O–C, and C–O. Py-GC/MS identified major pyrolysis products at both temperatures, before and after catalyst addition, as terpenoid derivatives, fatty acid derivatives, and aromatic and non-aromatic hydrocarbons. At 200 °C, the catalyst reduced the percent area of n-hexadecanoic acid while increasing the percent area of squalene, indicating enhanced deoxygenation activity. At 300 °C, the catalyst increased the percent areas of d-limonene, cyclohexane derivatives, and azulene. Overall, Ni/Ga-SBA-15 promoted the formation of terpenoid derivatives, while reducing the production of less desirable fatty acid derivatives. These results demonstrate that catalytic flash pyrolysis can modify product distribution from off-grade rubber.